Relationship between Clinicohistomorphology Profile of Atypical Prostate Gland and Diagnosis Benign Lesion or Prostate Adenocarcinoma - Litta Septina MZ; Yayi Dwina B (Majalah Patologi Indonesia, 2023)
BackgroundAtypical prostate gland especially atypical small acinar proliferation (ASAP) is a histopathological diagnosis that requires a follow-up biopsy 3-6 months after the first biopsy, because 17-60% of cases potentially to be malignant. The varied clinical and histomorphological characteristics of the atypical prostate gland make it difficult to confirm the final diagnosis as a benign lesion or prostate adenocarcinoma. This study aims to describe clinicohistomorphological cases of atypical prostate gland at Anatomical Pathology Department FKUI/RSCM and to identify histomorphological features of the atypical prostate gland as benign lesions or prostate adenocarcinoma on immunohistochemistry diagnosis.MethodsA histopathological investigation of prostate gland cases with atypical nuclei was carried out in 2011-2021 from archives of Anatomical Pathology Department FKUI/RSCM. Clinical and histomorphological characteristics were assessed and categorized into benign lesions or prostate adenocarcinoma based on immunohistochemistry appearance.ResultsThere were 109 cases of atypical prostate gland, 49 of which met the inclusion and exclusion criteria and could be analyzed. Corpora amylacea was found in 11 cases (84.6%) in the benign lesion group, statistically significant (p-value 0.005). Intraluminal crystalloids were found in 4 cases (100%) in the prostate adenocarcinoma group with p-value 0.050, close to significant. Other clinicohistomorphological characteristics did not show a significant relationship both in benign lesions and prostate adenocarcinoma groups (p-value 0.05).Conclusion On histopathological examination of the atypical prostate gland that is difficult to re-biopsy, the discovery of corpora amylacea may lead to the diagnosis of a benign lesion, while the discovery of intraluminal crystalloids may lead to the diagnosis of prostate adenocarcinoma. The diagnosis must be supported by immunohistochemistry characteristics.